Qualitative and quantitative determination of polycyclic aromatic hydrocarbons in fine particulate matter. Issue 4 (20th March 2020) - Naydenova, St.; Veli, A.; Mustafa, Z.; Gonsalvesh, L.
Abstract: A GC–MS method in SIM mode is proposed for routine analysis of nineteen polycyclic aromatic hydrocarbons (PAHs) in particulate matter with an aerodynamic diameter of 10 µm. The latter is collected on Whatman® QM–A quartz filters via OPSIS SM200 sampler during autumn and spring periods at two different points, i.e. the one affected from communal and industry sectors and the other affected mainly from the transportation sector. In order to recover PAHs of interest ultrasonic assisted extraction is employed by utilization of various solvents. Accuracy data of the developed analytical method are within acceptable limits for the studied concentration range, i.e. trueness 60.0–120.0% and precision < 20.0%. The elaborated methodology is characterized by advantages such as short extraction time, low solvent and reagent consumption and simplified cleaning and is successfully applied to airborne PM10, collected in the urban area of Burgas, Bulgaria.